Enhanced stability of vanadium-doped Li1.2Ni0.16Co0.08Mn0.56O2 cathode materials for superior Li-ion batteries. Issue 51 (16th November 2022) - Zhou, Miaomiao; Zhao, Jianjun; Wang, Xiaodong; Shen, Ji; Yang, Jin-Lin; Tang, Wenhao; Deng, Yirui; Zhao, Shi-Xi; Liu, Ruiping
Abstract : The high-valence V 5+ can improve the discharge capacity and coulomb efficiency and inhibit the voltage attenuation of cathode materials. Abstract : Lithium–manganese-based cathode materials have attracted much attention due to its high specific capacity, but the low initial coulomb efficiency, poor rate performance and voltage attenuation during cycling limit its application. In this work, Li1.2 Ni0.16 Co0.08 Mn0.56− x V x O2 samples ( x = 0, 0.005, 0.01, 0.02, 0.05) were prepared using the sol–gel method, and the effects of different V 5+ contents on the structure, valence state, and electrochemical performance of electrode materials were investigated. The results show that the introduction of high-valence V 5+ in cathode materials can reduce partial Mn 4+ to active Mn 3+ ions for charge conservation, which not only improves the discharge capacity and coulomb efficiency of Li-rich manganese-based cathode materials, but also inhibits the voltage attenuation. The initial discharge capacity of the Li1.2 Ni0.16 Co0.08 Mn0.55 V0.01 O2 is as high as 280.9 mA h g −1 with coulomb efficiency of 77.7% at 0.05C, which is much higher than that of the undoped pristine sample (236.6 mA h g −1 with coulomb efficiency of 74.0%). After 100 cycles at 0.1C, the capacity retention rate of Li1.2 Ni0.16 Co0.08 Mn0.55 V0.01 O2 was 92.3% with the median voltage retention rate of 95.6%. This work provides a new idea for high performance of lithium-rich manganese-based cathode materials.